(untitled) (Alberta Journal of Educational Research, 2021)
This investigation concerns school leaders’ perceptions regarding the efficacy of a leadership development initiative implemented across schools in the North Coast region of New South Wales, Australia. Based on an Alberta school improvement process, the North Coast Initiative for School Improvement sought to achieve leadership development and improved learning outcomes through use of the processes of collaborative inquiry and generative dialogue. Five schools were selected for an exploration of experiences within the Initiative. Accounts provided by the interviewees pointed strongly to the achievement of positive outcomes. The participants referred particularly to benefits in the form of increased leadership confidence and capability. Success factors underpinning the Initiative include: the twinning of collaborative inquiry as a process for improving professional practice with the process of generative dialogue to achieve more effective conversations, and; the nature of the Initiative, itself, where, facilitated by a visiting leadership team, professional colleagues meet monthly for deep discussion about professional issues they share. Key words: school improvement, school leadership, collaborative inquiry, generative dialogue, education innovation, change in educational practice. Cette enquête porte sur les perceptions des leaders scolaires concernant l’efficacité d’une initiative de développement du leadership mise en œuvre dans les écoles de la région de la côte nord de la Nouvelle-Galles du Sud, en Australie. Basée sur un processus d’amélioration des écoles de l’Alberta, la North Coast Initiative for School Improvement visait à développer le leadership et à améliorer les résultats d’apprentissage en utilisant les processus d’enquête collaborative et de dialogue génératif. Cinq écoles ont été sélectionnées pour une exploration des expériences au sein de l’initiative. Les comptes rendus fournis par les personnes interrogées ont mis en évidence l’obtention de résultats positifs. Les participants ont notamment fait référence à des avantages sous la forme d’une confiance et d’une capacité de leadership accrues. Les facteurs de réussite qui sous-tendent l’initiative sont les suivants : le jumelage de l’enquête collaborative en tant que processus d’amélioration de la pratique professionnelle avec le processus de dialogue génératif afin de parvenir à des conversations plus efficaces, et la nature de l’initiative elle-même, où, sous la direction d’une équipe de direction invitée, des collègues professionnels se rencontrent tous les mois pour discuter en profondeur de questions professionnelles communes. Mots clés : amélioration des écoles, leadership scolaire, enquête collaborative, dialogue génératif, innovation éducative, changement des pratiques éducatives